Legal Liability of Notaries for Authentic Deeds Containing Formal and Material Defects - Tjandraningsih, Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study explores the legal liability of notaries concerning authentic deeds that contain either formal or material defects. Notarial deeds hold conclusive evidentiary value in civil law, and therefore, any procedural or substantive error in their preparation can lead to serious legal consequences for both the involved parties and the notary. Using a normative juridical approach, the research analyzes statutory regulations, legal literature, and relevant court decisions. The aim is to examine the types and extent of notary liability civil, criminal, and administrative when a deed is proven to be defective, and to assess the legal protection available for parties harmed by such defects. The findings show that notaries may be held accountable if proven negligent or in breach of their legal obligations. In cases of formal defects, liability is generally administrative. However, for material defects that result in losses or involve intent, notaries may face civil claims or even criminal charges. Accordingly, this research underscores the importance of notaries performing their duties with diligence and in full compliance with the Notary Law to avoid potential legal disputes in the future.